SEVIMA EDLINK SOCIAL LEARNING NETWORK FOR NURSING SCIENCE STUDENTS AT STIK BINA HUSADA PALEMBANG - Agus Wahyudi (Language and Education Journal, 2020)
ICT is a valuable tool to enhance teaching and learning. The online class is Sevima Edlink, an android-based application that is devoted to the world of education which aims to provide a learning space that bridges the teachers and the students in learning activities that can be done anytime and anywhere with more flexible learning time. The features in this application that facilitate interaction between the teacher and the students namely: discussion forums, sharing features, assignments in class, info, events, and surveys. The research method used is qualitative research. The participants were the students of STIK Bina Husada in the academic year 2019/2020, majoring Nursing Science Study Program who were taking English 1 subject. There were19 students and in the 2nd semester. The use of this application was started on Tuesday, March 10, 2020, and ended on April 28th, 2020. This study aims to introduce the students’ Sevima Edlink application and describe their English performance or mid-semester result test as the evaluation. In general, the research on